The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3945/ajcn.116.147942
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-based nutrient supplementation in the first 1000 d improves child growth in Bangladesh: a cluster-randomized effectiveness trial

Abstract: Background: Stunting in linear growth occurs mainly during the first 1000 d, from conception through 24 mo of age. Despite the recognition of this critical period, there have been few evaluations of the growth impact of interventions that cover most of this window. Objective: We evaluated home fortification approaches for preventing maternal and child undernutrition within a community-based health program. We hypothesized that small-quantity lipid-based nutrient supplements (LNSs) provided to women during preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 28 publications
4
111
1
Order By: Relevance
“…However, among girls, there was a significantly lower proportion in the lowest quartile for executive function in the group who received LNSs postnatally compared with the control group (no difference was seen among boys). This finding may be linked to the greater impact of the RDNS intervention on head size in girls than in boys observed at 24 mo of age (13).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, among girls, there was a significantly lower proportion in the lowest quartile for executive function in the group who received LNSs postnatally compared with the control group (no difference was seen among boys). This finding may be linked to the greater impact of the RDNS intervention on head size in girls than in boys observed at 24 mo of age (13).…”
Section: Discussionmentioning
confidence: 66%
“…This report describes the effects of the RDNS intervention on child development (secondary) outcomes during the first 24 mo. Findings on the primary outcome of the RDNS (i.e., growth) are reported separately (13).…”
Section: Introductionmentioning
confidence: 99%
“…Point‐of‐use home fortification methods, such as micronutrient powders and small‐quantity lipid‐based nutrient supplements (SQ‐LNS), have the potential to fill in the nutrient gaps (Adu‐Afarwuah & Dewey, ). SQ‐LNS is also under investigation as a potential intervention to prevent stunting (Adu‐Afarwuah et al, ; Dewey et al, ; Hess et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies that compared LNS and MNP showed impacts of LNS, but not of MNP, on linear growth (12, 31). However, a key limitation of these studies is that the MNP supplements used have not included some macrominerals known to be important for growth (e.g., calcium, magnesium, phosphorus, and potassium) whereas they are typically included in LNS (32).…”
Section: Discussionmentioning
confidence: 99%